2018
DOI: 10.1038/s41398-018-0150-6
|View full text |Cite|
|
Sign up to set email alerts
|

GWAS on family history of Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is a public health priority for the 21st century. Risk reduction currently revolves around lifestyle changes with much research trying to elucidate the biological underpinnings. We show that self-report of parental history of Alzheimer’s dementia for case ascertainment in a genome-wide association study of 314,278 participants from UK Biobank (27,696 maternal cases, 14,338 paternal cases) is a valid proxy for an AD genetic study. After meta-analysing with published consortium data (n =… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
558
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 490 publications
(578 citation statements)
references
References 34 publications
19
558
1
Order By: Relevance
“…We obtained in total 63 modules (). GSEA with the GWAS gene set generated from Marioni et al (), at different cut‐offs for statistical significance as explained above (Fig A and ), demonstrated that the largest set of risk genes (e.g., n = 1,799 genes at P mar < 0.05) enrich among 4 APPtg‐ and TAUtg‐based modules (Turquoise, Blue, Fig A and ). However, when taking gene sets defined by increasing statistical significance ( P mar < 0.001 or smaller), the only module that persistently demonstrates significant enrichment with GWAS genes is the APPtg‐Blue module (see Fig A).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…We obtained in total 63 modules (). GSEA with the GWAS gene set generated from Marioni et al (), at different cut‐offs for statistical significance as explained above (Fig A and ), demonstrated that the largest set of risk genes (e.g., n = 1,799 genes at P mar < 0.05) enrich among 4 APPtg‐ and TAUtg‐based modules (Turquoise, Blue, Fig A and ). However, when taking gene sets defined by increasing statistical significance ( P mar < 0.001 or smaller), the only module that persistently demonstrates significant enrichment with GWAS genes is the APPtg‐Blue module (see Fig A).…”
Section: Resultsmentioning
confidence: 90%
“…In the genotype comparison, mRNA expression in all transgenic (TG) mice is compared to all wild‐type (WT) mice. In the age*genotype comparison, we assess which transcripts are differentially expressed in the 10M TG mice compared to all other groups. DBased on Marioni et al (), various sets of AD GWAS risk genes were created using different cut‐off P ‐values indicated on the x ‐axis (number of genes within each set is written in gray). Enrichment for AD risk genes was assessed among the different statistical comparisons for APPtg and TAUtg mice (A*G: age*genotype, Gen: genotype), using gene set enrichment analysis (GSEA, Subramanian et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower association signal for the 17q22 locus in the UK biobank cohort could be explained by differences in case ascertainment of AD. In the UK biobank, Alzheimer dementia is ascertained via self‐report information from family history (parent or a first‐degree relative with AD or dementia) as a proxy‐phenotype for the participants (Marioni et al, ). This method relies on people to provide accurate information about whether their parents developed AD, for which misclassification of case status is of greater concern than consortia relying upon clinician‐reported diagnoses.…”
Section: Discussionmentioning
confidence: 99%